2011
DOI: 10.1016/j.febslet.2011.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Role of magnesium ions in DNA recognition by the EcoRV restriction endonuclease

Abstract: Edited by Christian Griesingeris debated. Here, multiple independent molecular dynamics simulations suggest that Mg 2þ B is crucial for achieving a tightly bound protein-DNA complex and stabilizing a conformation that allows cleavage. In the absence of Mg 2þ B in all simulations the protein-DNA hydrogen bond network is significantly disrupted and the sharp kink at the central base pair step of the DNA, which is observed in the two-metal complex, is not present. Also, the active site residues rearrange in such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…Literature reports that Mg 2+ plays a functional role in the catalytic mechanism and the stability of protein-DNA complex. Metal ions also lower the local pKa, and this, considering the harsh environment that the organism experiences, is in a good agreement with our study [ 7 , 8 , 41 43 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Literature reports that Mg 2+ plays a functional role in the catalytic mechanism and the stability of protein-DNA complex. Metal ions also lower the local pKa, and this, considering the harsh environment that the organism experiences, is in a good agreement with our study [ 7 , 8 , 41 43 ].…”
Section: Resultssupporting
confidence: 92%
“…Endonucleases require one, two or three divalent metal ions, such as Mn 2+ or Mg 2+ in the catalytic site [ 7 13 ]. It is believed that in thermal environment, such as the one Thermotoga maritima lives in at temperatures around 80 °C, the most suitable metal ion for this kind of system is Mg 2+ [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[29] Theoretical study by Zahran et al shows that the second magnesium ion serves to stabilize the distorted DNA. [14] Our observations on the stability of the aspartic acids is qualitatively consistent to this theoretical report. Earlier studies show [38][39][40][41] that the residues which get conformationally destabilized and disordered participate in ligand binding.…”
Section: The Conformational Free Energy ðδGsupporting
confidence: 91%
“…performed to understand role of Mg 2+ as natural cofactor. [11,[14][15][16][17] But the microscopic origin of the specificity of metal ion cofactor Mg 2 + vis-à-vis Ca 2+ in DNA cleavage is unknown. [18][19][20] Naturally occurring restriction endonucleases are classified as four types such as type I, II, III and IV, depending on their structure, recognition site, cleavage site etc.…”
mentioning
confidence: 99%
“…Available high-resolution X-ray structures of many endonuclease enzymes in complex with target DNA or RNA or substrate analogues [31][32][33][34][35] and various biochemical studies have shown that metal cofactors are essential for the enzymatic phosphodiester cleavage [36][37][38][39]. The metal ions not only play a direct role in the chemical step but also influence the binding interaction of the enzyme with the DNA or RNA [40,41]. For some endonucleases different structures with different numbers of metal ions have been solved by X-ray crystallography under varying conditions [42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%